Soft X-ray and FUV observations of Nova Her 2021 (V1674 Her) with AstroSat - Bhargava, Yash (2023)
Nova Her 2021 or V1674 Her was one of the fastest novae to be observed so far. We report here the results from our timing and spectral studies of the source observed at multiple epochs with AstroSat. We report the detection of a periodicity in the source in soft X-rays at a period of 501.4–501.5 s which was detected with high significance after the peak of the super-soft phase, but was not detected in the far ultraviolet (FUV) band of AstroSat. The shape of the phase-folded X-ray light curves has varied significantly as the nova evolved. The phase-resolved spectral studies reveal the likely presence of various absorption features in the soft X-ray band of 0.5–2 keV, and suggest that the optical depth of these absorption features may be marginally dependent on the pulse phase. Strong emission lines from Si, N, and O are detected in the FUV, and their strength declined continuously as the nova evolved and went through a bright X-ray state.